Adsorption of Divalent Metal Ions on a Herbaceous Peat - DIKICI, HUSEYIN (Asian Journal of Chemistry, 2010)
This study was performed to determine divalent metal ion [Cu(II), Zn(II), Mn(II) and Ni(II)] adsorption characteristics of the herbaceous peat of the Gavur Lake, Turkey. The adsorption data of the metal ions were fitted to both the Langmuir and the Freundlich isotherms. The adsorption capacity of the peat was much higher for Cu (38.5 mg g-1) compared with Zn (28.0 mg g-1), Mn (26.4 mg g-1) and Ni (24.1 mg g-1). A steady increase in equilibrium Ca and Mg ion concentrations were measured as initial metal ion concentrations increased from 1 × 10-3 M to 5 × 10-3 M in Cu and Zn adsorption experiments indicating that ion exchange was an important mechanism in the adsorption. The kinetic study revealed that the adsorption followed the pseudo-second-order model and the interaction between the metal ions and the peat was very fast, especially for Cu. The pH study revealed that Cu adsorption was not affected in the pH range between 3 and 5, but the adsorption of Zn, Mn and Ni was lower at pH 3 compared with pH 4 and 5.